(untitled) (Balthazar, 2023)
In 18th century in France, the act of weeping in front of a painting was considered a pleasurable experience rooted in an emotional aesthetic. This concept found its theoretical basis in the writings of Jean-Baptiste Du Bos. According to him, the key to enjoying art was to sympathize with the emotions the artwork depicted. However, this emotional response to art also required moderation. While the spectator could engage with and experience the represented emotions, there was a need to maintain a certain distance (an aesthetic disinterest). In the context of the French eighteenth century, there was a strong belief that – in terms of ability to enjoy life and participate in society – the best individuals were those who possessed a high degree of sympathy. Sympathy was seen as a fundamental human characteristic that allowed individuals to connect with one another, foster relationships, and navigate social interactions.